Fiscal Policy, Economic Integration and Unemployment - Wolfgang Eggert; Laszlo Goerke (University of Copenhagen, Economic Policy Research Unit (EPRU), 2002)
Fiscal policy is examined in a model of an open economy which is characterised by unemployment caused by efficiency wages. It is shown that the conventional conclusion, according to which mobile capital is untaxed in the presence of wage taxation, is not generally valid. A positive capital tax allows to indirectly tax profits, thereby mitigating unemployment through the reduction in the effective tax burden on labour. It is argued that these policy conclusions are qualitatively unaffected by the cause of unemployment. Moreover, the welfare loss from labour market imperfections increases when tax bases become internationally mobile, which suggests an increasing relevance of domestic labour market reforms.
Keywords: 330; Finanzpolitik; Optimale Besteuerung; Kapitalertragsteuer; Arbeitslosigkeit; Effizienzlohn; Steuerwettbewerb; Kleine offene Volkswirtschaft; Wirtschaftsintegration; Theorie